1986
DOI: 10.1021/bk-1986-0312.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Procyanidin Interaction and Nutritional Quality of Dry Beans

Abstract: Thermodynamic analysis of the temperature dependance of procyanidin binding to bovine serum albumin (BSA) and bean glycoprotein G-1 suggested predominantly hydrophobic and hydrophilic binding, respectively. A cis-parinaric acid fluorescence assay for surface hydrophobicity supported amphiphilic interactions of procyanidin. Heat denatured G-1 had a surface hydrophobicity greater than native G-1. Procyanidin dimer and trimer inhibited trypsin digestion of BSA. In vitro digestibility and Tetrahymena-Protein Effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Artz et al (1986), phenolics are mainly localized in the cotyledons of the plants than in the hulls. Fig.…”
Section: Phenolics Characterization: Sinapine Sinapic Acid and Canolmentioning
confidence: 99%
“…According to Artz et al (1986), phenolics are mainly localized in the cotyledons of the plants than in the hulls. Fig.…”
Section: Phenolics Characterization: Sinapine Sinapic Acid and Canolmentioning
confidence: 99%
“…Commonly cultivated rapeseed varieties, including canola (Brassica napus and Brassica campestris), have a similar phenolic content Shahidi, 1989, 1992;Naczk et al, 1986Naczk et al, , 1998a. These are mainly located in seed cotyledons (Artz et al, 1986) and only trace amounts are found in seed coats. The total content of phenolic acids in various rapeseed protein products ranges from 1324.8 to 1837.0 mg/100 g of defatted meal and from 623.5 to 1280.9 mg/100 g of flour, on a dry weight basis (Table 3.3).…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…In our study, the apparent total tract digestibility (ATTD) of DM, N, energy, ash and Ca were decreased in the PRO treatment relative to the HES treatment. In vitro digestibility depression has been reported when procyanidins were intubated with food (Artz et al, 1986). Additionally, El-Sayed et al (2010) confirmed that nutrients digestibility improved in Nile Tilapia fed diets containing 5% dried citrus pulp.…”
Section: Discussionmentioning
confidence: 96%